Radiolabelling of steroids: the synthesis of 17α‐[4‐14C]trenbolone1. (19th August 2013) - Hendry, David; Knagg, Eric; Smith, Neil A.; Woolley, Geoffrey T.; Atzrodt, Jens; Derdau, Volker
<x xml:space="preserve">Abstract</x> 17β‐Hydroxyestra‐4, 9, 11‐trien‐3‐one or trenbolone is an anabolic steroid used in some meat producing countries where its use is licenced. In cattle it is metabolised into 17α‐trenbolone. We were required to make 17α‐[4‐14C]trenbolone for use in environmental fate studies. At the same time we also had a request to make 17α‐[4‐14C]estradiol so we combined the two syntheses and made use of the synergy to allow us to make a batch of 17α‐[4‐14C]estradiol by known methodology and then elaborate a portion of this into 17α‐[4‐14C]trenbolone. The synthesis of 17α‐[4‐14C]trenbolone from 17α‐[4‐14C]estradiol was achieved in 8 steps and 3.1% overall yield to give material with a radiochemical purity of 99.5% and specific activity of 59 mCi/mmol.